EFL Students' Perception towards the Use of Instagram in Speaking English - Aidah, Rachmah Shofiatul (RETAIN : Journal of Research in English Language Teaching, 2022)
Social media has gained massive popularity over the last ten years. As the result, social media is used in many different sectors including in education. As an educator, teachers can utilize social media as a tool to facilitate the student’s experiences, especially in language learning. Furthermore, among the popular social media, Instagram has been widely used in the educational field following its features where it is possibly used in language learning activities. Therefore, this study aims to investigate the secondary-level students' perceptions about the use of Instagram to practice speaking English in EFL classroom. This is a quantitative descriptive study that uses a survey to collect the data. Furthermore, a set of Likert-scale questionnaires with four option scales is used as the instrument. The population of the study was eleventh-grade students from one of a private schools in Surabaya. Furthermore, the sample of this study was 52 students taken by convenience sampling. The result of the study shows that the students see Instagram positively. The students find Instagram as a tool that provides a new way for them to practice speaking English. Instagram offers a different atmosphere for the students to practice, and it helps them to be more confident. Additionally, they also feel motivated.